Antidiabetic Activity and Analysis Chemical Compound of Fractions of Leucas lavandulifolia leaves - Carissa, Restri Diah; Yohandini, Heni; Muharni, Muharni (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2025)
Leucas lavandulifolia is one traditional medicine that has been used for the treatment of rheumatism, skin diseases, wounds, diabetes, and migraine treatment. This research aimed to test the antidiabetic activity of the leaf fractions of Leucas lavandulifolia and to identify the chemical content of the selected column fraction. Fractionation was carried out using the graded extraction method with the solvents n-hexane, ethyl acetate, methanol. Testing of antidiabetic activity was performed using the α-glucosidase inhibition method and analysis of the chemical composition content of the selected fraction was performed using the GC-MS method. The research results showed the Ethyl acetate fraction provided the highest antidiabetic activity (IC50 = 4.985 µg/mL) compared to the other fractions and even higher compared to the positive control acarbose (IC50 = 67.07 µg/mL). Separation of the ethyl acetate fraction showed subfractions F6.3 and F6.5 showed the simplest spot pattern. Identification of chemical content with GC-MS showed subfraction F6.3 contained the main component naphthalenepropanal derivative (17.21%) and subfraction F6.5 with the main component fatty acid. Subfractions F6.3 and F6.5 also showed antidiabetic activities with IC50 values of 17.3 and 36.72 µg/mL, respectively, with a very strong category. This indicates the ethyl acetate fraction of L. lavandulifolia leaves is potential to be developed as a source of antidiabetic compounds